Pengaruh Pengetahuan Kewirausahaan dan Lingkungan Keluarga Terhadap Minat Berwirausaha di SMA Negeri 3 Palangka Raya: The Influence of Entrepreneurship Knowledge and Family Environment Regarding Entrepreneurial Interest in SMA Negeri 3 Palangka Raya - Dadi, Eti Ambarsari; Suyati, Endang Sri; Rozikin, Achmad Zainul (Anterior Jurnal, 2025)
This research aims to: (1) determine the influence of knowledge and family environment on interest in entrepreneurship at SMA Negeri 3 Palangka Raya. The approach in this research is a quantitative approach with descriptive research methods.  The results of this research are 1) entrepreneurial knowledge influences interest in entrepreneurship at SMA Negeri 3 Palangka Raya. 2) the family environment influences students' interest in entrepreneurship at SMA Negeri 3 Palangka Raya. 3) entrepreneurial knowledge and family environment simultaneously influence the entrepreneurial interest variable.